The corporate cultivation of digital resignation in policymaking: How weak US regulations enable data trafficking to China - Aynne Kokas (Big Data & Society)
Studies of digital resignation focus on the idea of the corporate cultivation of digital resignation among users, an area of intense importance when examining user data sharing with corporations. To best appreciate the implications of digital resignation in a transnational context, it is important to consider not just resignation by users, but by policymakers. Weak digital policymaking in the US context enables continued digital resignation by users. It also allows for data trafficking, or government directed movement of user data across borders without clear user consent. This paper compares digital policymaking using three cases of national, regional, and sector-based digital policymaking. The commentary argues that while US policymakers often cast concerns on Chinese influence in the US, such arguments obscure the systematic resignation of US policymakers to a weak and ineffectual domestic digital oversight system. Examining digital resignation through a national government lens enables a more complete view of the transnational implications of this important concept.